World Database of Happiness Example of a focused `Findings Archive' - Ruut Veenhoven (Rat für Sozial- und Wirtschaftsdaten (RatSWD), 2011)
Social scientists are producing an ever growing stream of research findings, which is ever more difficult to oversee. As a result, capitalization on earlier investment declines and accumulation of knowledge stagnates. This situation calls for more research synthesis and interest in synthetic techniques is on the rise. To date attention has been focused on techniques for meta-analysis, with little attention paid to the preliminary step of bringing the available research findings together. What we need is 1) techniques for describing research findings in a comparable way, 2) a system for storing such descriptions in an easily accessible archive, 3) to which research findings can be added on a continuous basis. The World Database of Happiness is an example of such a tool. The archive is tailored to meet the requirements of assembling research findings on happiness; both distributional findings (how happy people are) and correlational findings (what things go together with happiness). With its focus on 'findings' the system differs from data-archives that store 'investigations' and from bibliographies that store 'publications'. As yet there is no established term to describe this tool for research synthesis. I call it a 'focused findings archive'. In this paper I describe how that works and discusses the strengths and weaknesses of this approach.
Keywords: D6; I3; E01; C38; 330; literature review; research synthesis; methodology; research archive; comparative analysis; happiness; life satisfaction; subjective wellbeing; quality of life; Zufriedenheit; Sozialforschung; Statistische Daten; Welt